2020
DOI: 10.1111/cxo.12897
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of angle kappa and pupil barycentre configuration in myopic tilted disc syndrome

Abstract: Background To evaluate the angle kappa and pupil barycentre configuration in patients with myopic tilted disc syndrome (TDS). Methods Thirty‐five eyes of 35 patients with TDS were included in the study. Thirty‐five eyes of 35 age‐ and sex‐matched healthy subjects were enrolled in the control group. All measurements were performed with the Lenstar LS 900. Angle kappa was calculated according to Pythagorean theorem using the x and y co‐ordinates of the pupil centre. Pupil dx and pupil dy values (pupil dx: x co‐o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…As delineated by the two formula D and E in Figure 5, y and x represent the projections of the step lengths on Y and X axes, respectively. The two catheti y, x and the hypotenuse s constitute a right-angled triangle (Figure 5), where the angular variation α a is easily computable by the inverse tangent formula C in Figure 5 (Dummer et al, 2016;Lin, 2019;Cankaya et al, 2020;Zhang et al, 2020). Of note, each step length s of the immune cell track is indissolubly linked to its relative α value conventionally referred to the X axis, as evidenced in Figure 5.…”
Section: Oncoimmuno Chip: a Specific Ooc System To Study Interactionsmentioning
confidence: 99%
“…As delineated by the two formula D and E in Figure 5, y and x represent the projections of the step lengths on Y and X axes, respectively. The two catheti y, x and the hypotenuse s constitute a right-angled triangle (Figure 5), where the angular variation α a is easily computable by the inverse tangent formula C in Figure 5 (Dummer et al, 2016;Lin, 2019;Cankaya et al, 2020;Zhang et al, 2020). Of note, each step length s of the immune cell track is indissolubly linked to its relative α value conventionally referred to the X axis, as evidenced in Figure 5.…”
Section: Oncoimmuno Chip: a Specific Ooc System To Study Interactionsmentioning
confidence: 99%
“…In refractive surgery, the kappa angle is a clinically important entity and may play a role in refractive results [6,7]. A wide kappa angle (0.6 mm) may cause misalignment errors during photoablation in laser refractive surgery and lens decentralization after multifocal lens implantation, leading to irregular astigmatism, photic phenomena (glare and halo), and decreased best-corrected visual acuity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although different methods are used to measure the kappa angle, the corneal re ection method, using a synoptophore or major amblyoscope, is used to measure the true kappa angle [8]. Orbscan II (Bausch & Lomb, Rochester, NY, USA), Galilei (Ziemer Ophthalmic Systems, Port, Switzerland), and OPD Scan II (Nidek, Gamagori, Japan) are the newer devices used to determine the kappa angle [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentacam has been more and more popular in measuring angle kappa for the past few years [7]. In addition, some reports have shown that Lenstar and iTrace were also commonly used to estimate angle kappa [8,9]. However, no published data has reported a comparison in the angle kappa among three devices.…”
mentioning
confidence: 99%